Child and Parent Predictors of Healthcare Utilization Amongst Children and Adolescents with Chronic Pain - Kathryn A. Birnie; Nivez Rasic; Melanie Noel (Canadian Journal of Pain, 2019)
Introduction/Aim: Pediatric chronic pain has a high economic burden. It is unknown what role parent factors have on healthcare utilization for pediatric chronic pain. Our aim was to identify child and parent factors that predict greater healthcare visits for pediatric chronic pain. Methods: 111 8- to 17-year-olds (M = 13.28; SD = 2.73; 67% female) and caregivers (89% female) attending an outpatient multidisciplinary pediatric chronic pain program. Children self-reported pain catastrophizing (PCS-C), and mobility, anxiety, depression, fatigue, and pain interference (PROMIS). Parents self-reported responses to their child’s pain (ARCS), pain catastrophizing (PCS-P), and their own chronic pain, physical function, anxiety, depression, fatigue, sleep, ability to participate in social roles, and pain interference (PROMIS). Healthcare utilization was parent-reported child visits to general practitioners, specialists, non-physician providers, emergency, and/or inpatient stays over the past 3 months due to pain. A linear regression assessed child (Step 1) and parent factors (Step 2) as predictors of healthcare utilization. Results: Number of pain-related healthcare visits over the past 3 months was 0 to 46 (M = 7.82; SD = 8.00). Healthcare utilization was significantly predicted by poorer child mobility (ß = .258; p < .05) and fatigue (ß = .362; p < .01; Step 1: R = .523; R2 = .273; F(10,100) = 3.76; p < .01). Parent factors did not add significantly overall (Step 2: R2 = .436; F(14,86) = 1.77; p = .06), although greater protective (ß = .299; p < .01) and less monitoring (ß = −.341; p < .05) behaviours, and greater ability to participate in social roles (ß = .258; p < .05) were significant predictors. Discussion/Conclusions: Greater healthcare utilization for pediatric chronic pain was primarily driven by child symptoms, with additional relations to parenting responses.